Development and application of a fully coupled eulerian thin film/discrete phase approach to a simplified aeroengine bearing chamber - Nicoli, Andrew (2020)
With a global drive to reduce emissions and improve fuel efficiency, aeroengine manufacturers are challenged with the significant task of developing more efficient engines. In order to achieve improved propulsion and thermal efficiencies, the desire to operate at both higher temperatures and shaft speeds requires sufficient understanding of the engine systems for design optimisation.